Italy : Technical Assistance Report-Enhancing Governance and Effectiveness of the Fiscal Agencies. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Assistance Report discusses measures to enhance the effectiveness of tax administration system in Italy. The Italian tax administration system comprises multiple entities, which demands tight coordination. Tax revenues are high, but collection performance in the main taxes is mixed. The agencies' accountability framework to the Ministry of Economy and Finance is very detailed and should be more strategic. The agencies have not been empowered to develop their own medium-term strategic plan. A holistic approach to managing risks to the tax system is needed, including targeted compliance strategies. The accumulation of tax debts is alarming, and structural issues need to be addressed urgently.